Overcoming the Problem of Speaking Ability of Lower Grade Elementary School Students with the Kipin School Application - Gui, Marsella Desriyarini (Edumaspul: Jurnal Pendidikan, 2026)
Assessment (AN) shows that level literacy student school elementary school (SD) still low. One in two students at the elementary school level has not reach minimum literacy competency. This means that many student We Still difficulty understand information from the text they read, far from demands skills modern literacy. As a result, students No own sufficient ability​ in various aspect skills language skills required at the level school this basis. Improve ability speak is one of the skills that become attention for school teachers basic. Ability speak is the ability to express, state, and convey thoughts, ideas, and feelings through use sounds articulation or words. This research aims to improve skills speak Elementary School Students Low by using application Kipin School as Digital Literacy. In this study, the method studies library used by using secondary data, namely data obtained from books and articles in journals local and international on the internet. Kipin School Application, skills speaking, and elementary school children Low is topic discussion. Data taken from books and articles published in Indonesia and around the world. The data collection method used Mary W. George's theory and applying the research process studies library consisting of from nine steps. Research results show that ability speak student class low must sharpened and trained moreover first by using application Kipin School as a digital literacy medium. By using book digital stories and folklore videos available at Kipin School, as well as appropriate learning strategies, elementary school students in grades low can increase ability speak them and use his ability to read and write .